Therapeutic comparison in psychological capital - Chan, Gloria Hongyee (Frontiers in Psychiatry, 2023)
Aim: This study aimed to investigate and compare the therapeutic outcomes of psychological capital between narrative therapy, cognitive-behavioral therapy, and play therapy in the context of hikikomori. Methods: This study included 502 hikikomori. Correlation analysis was performed to investigate the relationship between the three forms of therapy and psychological capital, while one-way ANOVA and independent samples t-tests were performed to determine the differences in the outcomes of psychological capital between the three forms of therapies. Results: Results indicated that all three forms of therapy were significantly positively related to psychological capital. Moreover, while cognitive-behavioral therapy performed better in psychological capital (overall score) than the other two, cognitive-behavioral therapy performed better in the subscales "self-efficacy" and "resilience," while narrative therapy performed better in the "hope" and "optimism" subscales. Also, combining features of play therapy helped enhance the outcomes of narrative therapy and cognitive-behavioral therapy on psychological capital. Conclusion: Owing to the varied outcomes of psychological capital among different therapies, the differential use of therapies to deal with the unique needs resultant of hikikomori helps achieve optimal results.